A non-contractual approach to smart contracts - GAMPER, Florian (Institutional Knowledge at Singapore Management University, 2023)
This article adds to the debate on what, legally speaking, smart contracts are and what they should be. Currently, much of this debate focuses on the relationship between smart contracts and legal contracts, overlooking that other legal categories may also be appropriate. This article suggests that the concept of abandonment can be fruitfully applied to smart contracts. Using the concept of abandonment has the advantage of allowing smart contracts, as close as legally possible, to be utilized as machines (or using the terminology suggested by Vitalik Buterin, founder of Etherium, as a ‘persistent script’). It would also make other issues, like the interpretation of smart contracts, easier to deal with. The argument is not that smart contracts can never be legal contracts; rather, it is suggested that, prima facie, users should have the choice of utilizing smart contracts as legal contracts or as machines.